(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
The contemporary business environment places demands on companies to go beyond economic survival and self-interest and satisfy the needs of various stakeholders. Organizations embark on the path of responsibility and sustainability, but many argue that CSR becomes embedded in an organization when it permeates all aspects of organization, including the organizational culture. Existing organizational culture typologies only provide the framework for analysis within the traditional business paradigm, but they are of limited use in the context of corporate social responsibility. After the analysis of major scholarship in the field, this paper defines CSR culture and identifies four types of organizational cultures based on companies’ CSR orientations, namely CSR-related values and strategy. In order to fully embed CSR culture, CSR has to be both strategic and value driven. This paper explores different CSR orientations and makes recommendations needed in order to achieve the desired state. Furthermore, through exploratory factor analysis, it identifies two cultural elements, CSR values and employee engagement in CSR, which indicate the existence of CSR culture. Identification of these cultural elements is intended to help in analyzing the direct and indirect effect of CSR culture on organizational outcomes, especially employee attitudinal and behavioral outcomes. Keywords: Corporate social responsibility, organizational culture, strategy, values, employee engagement